Pro Oracle Database 18c Administration : Manage and Safeguard Your Organization's Data - Malcher, Michelle; Kuhn, Darl (Expert's voice in Oracle., 2019)
Chapter 3: Configuring an Efficient Environment; Customizing Your OS Command Prompt; Customizing Your SQL Prompt; Creating Shortcuts for Frequently Used Commands; Using Aliases; Using a Function; Rerunning Commands Quickly; Scrolling with the Up and Down Arrow Keys; Using Ctrl+P and Ctrl+N; Listing the Command History; Searching in Reverse; Setting the Command Editor; Developing Standard Scripts; dba_setup; dba_fcns; tbsp_chk.bsh; conn.bsh; filesp.bsh; login.sql; top.sql; lock.sql; users.sql; Organizing Scripts; Step 1. Create Directories; Step 2. Copy Files to Directories